2014
DOI: 10.1016/j.bbamcr.2013.11.024
|View full text |Cite
|
Sign up to set email alerts
|

GSTpi protects against angiotensin II-induced proliferation and migration of vascular smooth muscle cells by preventing signal transducer and activator of transcription 3 activation

Abstract: Angiotensin II (Ang II)-elicited excessive proliferation, hypertrophy and migration of vascular smooth muscle cells (VSMCs) are vital to the pathogenesis of atheroclerosis. Glutathione S-transferase pi (GSTpi) exists extensively in various kinds of cells and protects cells against different stresses. However, knowledge remains limited about what GSTpi acts in VSMCs. We investigated the effect of GSTpi on Ang II-induced VSMC proliferation, hypertrophy and migration and its latent mechanism. Overexpression and R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 28 publications
1
23
0
Order By: Relevance
“…We also found that GSTpi could bind tumor necrosis factor receptor-associated factor 2 (TRAF2) in the TRAF domain to block the TRAF2-apoptosis signal-regulating kinase 1 (ASK1)-JNK signaling cascade induced by TNF-α, and as a result, inhibited cell apoptosis [15]. Furthermore, GSTpi prevented the proliferation and migration of vascular smooth muscle cell [16]. These results all suggest that GSTpi might regulate endothelial barrier function in ECs.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…We also found that GSTpi could bind tumor necrosis factor receptor-associated factor 2 (TRAF2) in the TRAF domain to block the TRAF2-apoptosis signal-regulating kinase 1 (ASK1)-JNK signaling cascade induced by TNF-α, and as a result, inhibited cell apoptosis [15]. Furthermore, GSTpi prevented the proliferation and migration of vascular smooth muscle cell [16]. These results all suggest that GSTpi might regulate endothelial barrier function in ECs.…”
Section: Discussionmentioning
confidence: 93%
“…WhenTyr7 is substituted with Phe, the transferase activity of GSTpi decreases by 55 times [16]. Since most of the function of GSTpi is related to its enzyme activity, we investigated whether inhibition of the increase of TNF-α-induced EC permeability was related to GSTpi transferase activity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Angiotensin II is also implicated in the pathophysiological processes related to myocardial remodeling [10, 11]. Angiotensin II activates several nuclear transcription factors (such as signal transducer and activator of transcription (STAT) and cyclic adenosine monophosphate (cAMP) response element-binding (CREB) protein) by promoting fibroblast proliferation that leads to myocardial remodeling [12,13]. …”
Section: Introductionmentioning
confidence: 99%